'Civil Society': Anatomi Perkembangan Perkumpulan Warga di Era Otonomi - Bambang Hudayana (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2003)
Observation at rural grassroots in Special Province of Yogyakarta reveals that there is a strong foundation for civil society. Self governing capacity has been well demonstrated in many forms within the daily live of the community: neigbourhood associations, policy advocacy and so on. The way they organise them mostly by revitalised the disfunctional organisation during the New Order government. Yet, more external fascilitation and support is needed still.